Assaying RNA structure with LASER-Seq. Issue 1 (22nd November 2018) - Zinshteyn, Boris; Chan, Dalen; England, Whitney; Feng, Chao; Green, Rachel; Spitale, Robert C
Abstract: Chemical probing methods are crucial to our understanding of the structure and function of RNA molecules. The majority of chemical methods used to probe RNA structure report on Watson–Crick pairing, but tertiary structure parameters such as solvent accessibility can provide an additional layer of structural information, particularly in RNA-protein complexes. Herein we report the development of Light Activated Structural Examination of RNA by high-throughput sequencing, or LASER-Seq, for measuring RNA structure in cells with deep sequencing. LASER relies on a light-generated nicotinoyl nitrenium ion to form covalent adducts with the C8 position of adenosine and guanosine. Reactivity is governed by the accessibility of C8 to the light-generated probe. We compare structure probing by RT-stop and mutational profiling (MaP), demonstrating that LASER can be integrated with both platforms for RNA structure analyses. We find that LASER reactivity correlates with solvent accessibility across the entire ribosome, and that LASER can be used to rapidly survey for ligand binding sites in an unbiased fashion. LASER has a particular advantage in this last application, as it readily modifies paired nucleotides, enabling the identification of binding sites and conformational changes in highly structured RNA.